(untitled) (Central Asian Journal of Medical Sciences, 2025)
Objective: To develop a herbal preparation for respiratory ailments from plants used in Mongolian medicine. Method: TLC, HPLC, chemical and spectrophotometric analysis were used for the quality and quantitative determination of biologically active compounds in plant raw materials, extracts and granules. The total and internal absorption coefficients of the plant raw materials, tapped density and flowability of the granules were determined using the method of I.A. Muravyev and V.D. Ponomarev. The quality parameters of the granules (appearance, particle size, moisture content, dispersion) were determined by the Chinese pharmacopoeia methods. Results: The highest amount of extractive matters was determined when extracting 2 mm powdered roots of Glycyrrhiza uralensis Fisch.ex DC. using 0.25% ammonia (34.46±3.01), 2 mm powdered roots of Inula helenium L. with 50% ethanol (56.69±2.83), and 2 mm powdered fruits of Rosa acicularis Lindl. with 40% ethanol (32.15±1.62). The glycyrrhizic acid content in the root of Glycyrrhiza uralensis Fisch.ex DC. was measured at 3.51±1.73%. Similarly, the inulin content in the root of Inula helenium L. was found to be 5.56±0.003%, and the ascorbic acid content in the fruits of Rosa acicularis Lindl. was also identified as 1.91±0.1%. After determining the extractive matters, particle size, total and internal absorption coefficients, and the content of majn biologically active compounds in the plant materials, liquid extracts were obtained from the plant raw materials, and thick extracts were prepared from these liquid extracts. The main substances in the liquid and thick extracts were identified and quantified. The glycyrrhizic acid content was 1.04±0.01% in the liquid extract and 2.87±0.08% in the thick extract; the ascorbic acid content was 0.47 ± 0.06% in the liquid extract and 0.73 ±0.06% in the thick extract; and the inulin content was 4.72±0.002% in the liquid extract and 15.07±0.002% in the thick extract. Five different models of granules were prepared from thick extracts using the wet granulation method. Model 1 granules were excluded from the study due to their irregular texture, clamminess, and inability to be sieved. The quality and technological parameters of the granule F2 model were superior to those of the other models (P<0.001). Granule model F2 contains 0.092±0.002% glycyrrhizic acid, 2.153±0.049% inulin, and 0.27±0.03% ascorbic acid. The prepared granules met the criteria for the microbiological test. Conclusion: It is suitable to extract the roots of Glycyrrhiza uralensis Fisch.ex DC., the root of Inula helenium L., and the fruits of Rosa acicularis Lindl. by powdering them into 2 mm particle sizes. Of the five models of granules prepared by wet granulation from plant extracts, model 2 was superior to the others in terms of technological and quality parameters. Sucrose was not suitable for granulation as an excipient.